Generalized implicit fear associations in generalized anxiety disorder. - Reinecke, A; Becker, E; Hoyer, J; Rinck, M (2010)
BACKGROUND: Cognitive schema theories of anxiety postulate that higher-level cognitive processes such as attention and memory are guided by underlying distorted fear associations. While numerous studies investigated these disorder-specific, biased processes, hardly any research addressed the underlying schemata themselves. In particular, no study has ever addressed implicit fear associations in Generalized Anxiety Disorder (GAD). In addition, no study has ever experimentally investigated the clinical observation that in GAD, patients' worry processes seem to be triggered by a broad range of materials, even by neutral or positive stimuli. METHODS: We used a Single Target Implicit Association Task (STIAT) to investigate implicit associations and stimulus generalization with clearly negative worry-related words (e.g., cancer, bankruptcy) and neutral words that are only indirectly related to worry topics (e.g., doctor, bank). Participants were 39 GAD patients and 23 healthy controls. RESULTS: In line with our expectations, both groups showed negative implicit associations with negative target words, and only GAD patients also associated neutral words with negative attributes. CONCLUSIONS: These results support the hypothesis that GAD patients' fear associations generalize to stimuli that are only peripherally related to the core of their worries.